In Silico Strategy to Control or Treat Nipah Virus Infection in Humans Through Saikosaponin Biomolecules - Dr. Sriparna Ray; Dr. Jayanta Sinha (International Journal of Pharma and Bio Sciences, 2022)
The penetrance of deadly Nipah virus causing high mortality in humans is mediated by bats and pigs, and there is lack of licensed drugs against it till date. In India the transmittance is caused among humans through direct contamination of secretion and excretion. In order to combat the fatal Nipah virus, so far one strategy has been concerned in this paper; exploiting extract and resources that are of botanical origin. Usually in India, Favipiravir (T-705) is used as anti-viral medicine against Nipah virus. Chemically it is a pyrazinecarboxamide derivative and is an experimental antiviral drug being developed by Toyama Chemical of Japan with activity against many RNA viruses. As Favipiravir is a synthetic analogue, it may cause some side effects in renal function. This paper aims towards identifying various Saikosaponins as an anti-Nipah viral agent and establish its efficacy in binding of these molecules with a viral phosphoprotein. Thus with such an aim and considering the limitation of synthetic drugs, this paper focuses on the interaction between Nipah virus and natural bioactive compounds Saikosaponins (A, B2, C, D, etc.), which are triterpene glycosides (naturally occurring) being isolated from medicinal plants such as Bupleurum spp, Heteromorpha spp, and Scrophularia scorodonia. Molecular docking of these herbal compounds with Nipah virus phosphoprotein was carried out through Molecular docking server. Lower energy scores represent better binding between Nipah virus phosphoprotein target and Saikosaponins as ligands. It is observed that best binding occurred between Nipah virus and saikosaponins K among the Saikosaponins clearly indicates its importance to be served as a potent drug. Ligplot+ server revealed polar and hydrophobic residues mainly involved in docking.